Treasure Island Level 2 - Stevenson, Robert Louis; Ward, Ann; Hopkins, Andy; Potter, Jocelyn (England Pearson Education Ltd, 2008)
This book is about Jim Hawkins and his parents who have a quiet inn by the sea. Then one day, an old sailor came to the inn. What is he afraid of? Dangerous men arrive at the inn. Jim's quiet life changes and he crosses the ocean by ship to Treasure Island.
Keywords: Tham khảo